Pengaruh Lingkungan Kerja, Beban Kerja, dan Gaya Kepemimpinan terhadap Kepuasan Kerja Karyawan: (Studi Pada Karyawan Non Medis Klinik Daya Medika Jakarta Barat) - Syifa Nur Andiefa; Hari Subagio (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study aims to investigate the influence of Work Environment, Workload, and Leadership Style on Job Satisfaction among Non -Medical Employees at Daya Medika Clinic in West Jakarta. This study used a Likert-scale questionnaire and involved a sample of 43 employees using a non-probability sampling method and saturated sampling technique. The results of a multiple linear regression analysis using SPSS version 26 indicate that Work Environment has a positive and significant effect on Employee Job Satisfaction, Workload has no significant effect on Employee Job Satisfaction, while Leadership Style has a positive and significant effect on Employee Job Satisfaction. These findings provide insights for Daya Medika Clinic management in improving the quality of the work environment and implementing appropriate leadership styles to enhance employee job satisfaction. These findings have practical implications for improving employee performance and organizational effectiveness, and serve as a reference for further research in the field of human resource management.